Transformation of Electronic Technology through the Application of e-Syariah and i-Syariah Systems in the Syariah Court Case Management System in Malaysia: (Transformasi Teknologi Elektronik Melalui Aplikasi Sistem E-Syariah dan I-Syariah dalam Sistem Pengurusan Mahkamah Syariah di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2022)
The implementation of information technology in the Syariah Judiciary Institution has been well received by all Syariah Courts throughout Malaysia through the application of the e-Syariah system. The innovation and electronic technology transformation has been continued in several Syariah Courts, including the Syariah Court in Sarawak that developed a new system called the i-Syariah, or Syariah Intelligence Management System. This research paper is aimed at analysing the development of the Syariah Court Case Management System through the e-Syariah system at the federal level and the i-Syariah system that is applied in Sarawak. Analysis was also done on the modules developed in the e-Syariah and i-Syariah systems to acquire comprehensive research information. A qualitative research methodology was applied to the progress of e-Syariah and i-Syariah systems' development and a comparative methodology was applied to compare the systems applied in the Civil Court with the contents of systems applied in the Syariah Judiciary Institution. The research found that the electronic technology transformation in the Syariah Court has shown less development compared to that of the Civil Court, which applies e-Filing system (EFS), Case Management System (CMS), Queue Management System (QMS), Court Recording and Transcribing (CRT), Artificial Intelligence (AI) and Community and Advocate Portal System (CAP). However, according to the i-Syariah development plan, various applications that are used in the Civil Court will be implemented in the Sarawak Syariah Court to ensure that the information and communication technology (ICT) transformation is in line with the digital technology development in Sarawak.Keywords: e-Government, i-Syariah, e-Syariah, Syariah Court Case Management System, Sarawak Syariah Judiciary Department, Syariah judicial institutionFull text: PDF